Pengaruh Modulus Aktivator (Na2SiO3/NaOH) Terhadap Kuat Tekan Mortar Geopolimer Abu Terbang Dengan Perawatan Suhu Ruang - Ali Imron Rusadi; Alfian Kamaldi; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Geopolymer is a material made without cement mixture by utilizing waste material such as fly ash, palm ash and husk ash and other materials that are rich in silica and alumina, and activated using solution activators such as NaOH and Na2SiO3. This study examines the characteristics of fly ash and the effect of activator modulus (Ms) on the compressive strength of mortar with the treatment of room temperature. Fly ash used was sourced from PLTU Ombilin, West Sumatra. The variations of activator modulus used were Ms 1, 1.5, 2, 2.5, and 3. The mold used was cube with the size 5x5 cm. The speciments were casted and treated in the laboratory under room temperature condition. The compressive tests were performed at 7, 14, and 28 days of mortar age. The results showed that the fly ash used was included in class F in accordance with ASTM C 618. The compressive strength test showed that there was an increase in compressive strength as the test age increased in all variations of the activator modulus. The highest value of compressive strength was produced by mortar geopolymer with modulus activator 2 which was 11.2 MPa at 28 days, while the lowest compressive strength was produced by mortar with modulus activator 2.5 with difference 19.14% at age 28 day. Key words : mortar, compressive strength geopolimer mortar, room temperature, siactivator iiimodulus